Effect of cationic polyelectrolytes addition in cement cohesion (2014)
Here is studied the variation in cohesion of cement main phase (C-S-H) as a result of cationic polyelectrolytes addition (quaternary amines spermine and norspermidine). Cohesion study was carried out by molecular simulation techniques (Monte Carlo) using a primitive model in a canonical ensemble (NVT). The proposed model takes into account the influence of ionic size of each particle and the addition of polyelectrolytes with different charge number and separation. The results obtained show that electrostatic interactions are responsible for the cohesion of the hardened cement. It was found that in absence of cationic polyelectrolytes, cohesion is lost when the C-S-H lamellae are at separations larger than 1 nm. Adding cationic polyelectrolytes generates a distribution of hydroxide ions around the polyelectrolyte charges, facilitates the distribution of calcium and sodium ions in the entire space between C-S-H surfaces; this allows the cohesive forces exist at greater distances of separation between the surfaces.